Implementing Kansei Engineering and Quality Function Deployment Method in Designing Shoes : Case Study at Rejowinangun Original Leather - Hapsoro Agung Jatmiko; Danov Setiyo Nugroho (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
SME played an important role in the economic growth in Indonesia, as Yogyakarta one of it’s promising province with relied so much on tourism and art and creative business, SME has become one of the main source of income for Yogyakarta. Rejowinangun Original Leather is one of SME in Yogyakarta that creates and produces its own hand made shoes. Not only producing themselves, this SME also buy several shoes product from another province, which ironically sells better than their own. One of the main concern of the failure in sale is the poor design of the self-made shoes. If the SME cared about their own design, it could be their selling point in order to survive and even played as an one of the big player in shoes industry. This research implementing both Kansei and QFD on the design of the shoes, thus collecting what the customer needs and creating the best design for the SME. The outcome of this research is the newly designed shoes based on what the customer needs, the shoes hopefully can also be used as a new branding image for the SME.